Evaluation of chromosomal abnormalities and copy number variations in late trimester pregnancy using cordocentesis - Cai, Meiying (Aging (Albany NY), 2020)
Because the numbers of detected fetal abnormalities increase as gestation progresses, we evaluated the safety and efficacy of cordocentesis for single nucleotide polymorphism (SNP) analysis tests in 754 women during third trimester pregnancy. Conventional karyotyping was performed on all fetuses, and Affymetrix CytoScan HD was used for SNP-array testing. In addition to the 24 cases with chromosomal abnormalities detected with conventional karyotyping analysis, the SNP-array test identified 56 (7.4%) cases with normal karyotypes but abnormal copy number variations (CNVs). Of those, 24 were pathogenic CNVs and 32 were of uncertain clinical significance. In 742 of the cases, there were abnormal sonographic findings, and cytogenetic abnormalities were detected in 76 cases (10.2%). The largest number of abnormalities involved multiple malformations (21.7%), followed by defects in the lymphatics or effusion (19.0%) or urogenital system (15.3%). The use of SNP-array test fully complemented chromosome karyotype analysis after late cordocentesis. It also improved the detection rate for fetal chromosomal abnormalities and was effective for preventing and controlling the occurrence of birth defects.